Analysis of Students' Mathematical Communication Skills On The Material of Two-Variable Linear Equation System With The Application of Bruner Theory - Sariayu, Sariayu; Hasratuddin, Hasratuddin; Sinaga, Bornok; Rajagukguk, Waminton (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
The subjects of this qualitative descriptive research were class VIII students of SMP Negeri 4 Tarutung located in North Tapanuli Regency. The aim of this research is to determine and explain students' mathematical communication abilities when solving problems using Bruner's Theory. The data is in the form of written test results given to students to assess their mathematical communication skills in solving problems using Bruner's Theory. The results of the interview also consist of students' answers to verbal questions given to obtain additional information. Documentation data in the form of pictures and archives of test answers taken by class VIII students of SMP Negeri 4 Tarutung. Data collection methods include written tests, interviews, and documentation. Data analysis is carried out by reducing data, presenting and drawing conclusions. The results of the research show that students' mathematical communication skills when solving problems use Bruner's Theory 43% of students with high mathematical communication skills were able to solve questions correctly and well, while 36% of students with moderate abilities could only meet some indicators, and 21% of students with low abilities could not meet all the indicators.